PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS DISCOVERY LEARNING PADA KOORDINAT KARTESIUS SMP KELAS VIII - Dea Septi Risda (Departemen Matematika, 2020)
The purpose of this research is to develop student worksheets (LKPD) based on discovery learning that is valid and practical on Cartesian coordinates for grade VIII junior high school students. This research is a development research by modifying the Plomp development model which consists of three phases, namely preliminary research, prototyping stage, and the assessment phase. Based on the results of data validity analysis in terms of four aspects, namely the feasibility of content, linguistic aspects, presentation aspects and graphic aspects, it shows that the-based student worksheets discovery learning have a validity level of 87,33% with a category very valid. In the practicality category, LKPD also met the practical criteria from the result of the questionnaire responses of three students who had carried out the one to one evaluation with a persentage of 89,26%. Based on these results it can be concluded that based student worksheets discovery learning on Cartesian coordinates for grade VIII junior high school students can be declared valid and practical. Keywords – Development Research, Student Worksheet, Discovery Learning